Nano-structure tin/nitrogen-doped reduced graphene oxide composites as high capacity lithium-ion batteries anodes - Jarulertwathana N. (2017)
© 2017 Springer Science+Business Media, LLC Tin/graphene-based composites were synthesized as easy-to-prepare alternative anode materials in lithium-ion batteries (LIBs). Reduced graphene oxide (rGO) was obtained from the oxidation of pristine graphite by modified Hummers’ method followed by thermal treatment at 500 °C for 5 h under N 2 atmosphere. Nitrogen-doped graphene (NrGO) sheets were prepared via thermal annealing of rGO and melamine (1:5 by weight) at 800 °C for 1 h under N 2 environment. The chemical reduction method was used to synthesize the composites. The Sn content in Sn/rGO and Sn/NrGO was varied as 10 and 20 wt%. The rGO and NrGO supporting materials had large surface areas and were exfoliated graphite structure. The powder X-ray diffraction patterns showed that Sn/rGO and Sn/NrGO composites contained Sn and graphene-based supporter. The electron microscopic measurements granted the composite morphology, in which they consisted of small Sn particles anchored on rGO and NrGO surfaces. The 20Sn/rGO and 20Sn/NrGO composites delivered large reversible specific capacities of 793 and 755 mAh g − 1 , respectively, at a current density of 100 mA g − 1 . The prepared composites also provide high stability, indicating the promising anode performance for LIBs.